Numerical Investigation of Natural Convection Flow in a Hexagonal Enclosure Having Vertical Fin - Asad, M. Fayz -Al-; Sarker, M. M. A.; Munshi, M. J. H. (Journal of Scientific Research, 2019)
Numerical study of natural convection flow in a hexagonal enclosure with a single vertical fin attached to its heated bottom wall has been carried out. Finite element method based Galerkin weighted residual technique is used to solve the governing equation. The horizontal walls of the enclosure are kept at constant high temperature while the inclined walls are kept at constant cold temperature. A vertical heated fin is attached to the hot bottom wall with a length at a position from the left surface having thickness . The Prandlt number for the flow inside the enclosure is 0.71. The results of the problem are presented in graphical and tabular forms and discussed. The fin efficiency and temperature distribution were examined. The numerical results indicate the strong influence of the mentioned parameters on the flow structure and heat transfer as well as temperature. A set of graphical results are presented in terms of streamlines, isotherms contour, temperature profiles, velocity profiles, local Nusselt number and average Nusselt number. The obtained results indicated that the heat transfer rate increases with the increase of Rayleigh number in a hexagonal enclosure. The results are validated comparing with the published works.